Designing for Participatory Governance: assessing capabilities and toolkits in public service delivery. Issue 6 (19th August 2014) - van der Graaf, Shenja; Veeckman, Carina
Abstract : Purpose: This study is designed to yield insight into how cities can optimize citizen involvement in the co-development of citizen services, by providing the rights tools, knowledge and resources. Design/methodology/approach: By conducting a case study analysis of the city of Ghent, this study investigates how users are engaged in the development of mobile applications on a city-hosted platform. Findings: Findings show that public service delivery, related to the urban space, can be co-designed between the city and its citizens, if different toolkits aligned with the specific capacities and skills of the citizens are provided. Research limitations/implications: Data was collected between August 2012 and December 2013. Some preliminary findings are presented on the (design of the) dynamic co-creation ecosystem and the citizens' capacities to participate on the city-hosted platform. And, while the examination is still on-going some insights can be offered in the learning dynamics underpinning how the cities are setting up such a bottom-up process and how local participation for different citizen groups can be optimized in the context of design capabilities and the design space. Originality/value: This study yields relevant insights for policy makers, city administrations as well as living lab practitioners into how public service delivery supported by an inclusive participatory governance by design framework at the local level, can be co-designed between the city and citizens, if different toolkits aligned with the specific capacities and skills of the users, are provided. By providing tailored tools even ordinary citizens can take a much more active role in the development and appropriation of their urban space and generate solutions from which both the city and citizens' everyday life can possibly benefit.